Lyme disease in a warming world - Randi Shupp; Elyse Watkins (JAAPA, 2026)
ABSTRACT Lyme disease, the most common vector-borne illness in the United States, is increasingly affecting regions beyond historically endemic areas. Warming temperatures and evolving ecosystems have contributed to the expansion of tick populations and altered seasonal activity, raising the likelihood of human exposure in areas previously considered low-risk. Clinicians must maintain a high index of suspicion for Lyme disease, even in patients without traditional geographic exposure. This article reviews the impact of environmental changes on the distribution and epidemiology of Lyme disease. It also provides an overview of clinical presentations, diagnostic strategies, and treatment recommendations. Emphasis is placed on early recognition, appropriate use of serologic testing, timely antibiotic therapy, and preventive measures to reduce disease burden. Awareness is crucial for delivering effective patient care and preventing complications in an evolving epidemiologic landscape.